Contribution des zones d'échanges entre eau de surface et eau souterraine à la biodiversité des hydrosystèmes : exemple d'une rivière méditerranéenne, la Cèze - Pierre Marmonier; Marie-José Dole-Olivier; Michel Creuzé des Châtelliers; Hervé Chapuis; Jordan Re-Bahuaud; Anne Johannet; Laurent Cadilhac (Physio-Géo)
In a close future, Mediterranean rivers will support strong disturbances due to climate changes, with inexorable consequences for their fauna. The invertebrate biodiversity of the Cèze River (South of France) was studied in a karstic area. The benthic layer (river bottom), the hyporheic layer (interface with the groundwater inside river sediment) and the lateral springs (interface with the karstic systems) were sampled in early summer. Only 11 % of the taxa were sampled simultaneously in the three habitats. Ephemeroptera and Trichoptera were more species rich in the benthic zone; Oligochaetes, crustaceans and Plecoptera in the hyporheic zone and Diptera in the lateral springs. Stygobite species lack in the benthic layer, they were more diversified in the springs and in the hyporheic zone. When all habitats are considered together, the total taxonomic richness is twice of the benthic one. The habitats located at the interface between river and groundwater thus must be included in the river biodiversity estimations.